Model to increase motivation and learning outcomes in learning history - Wa Ima; Johan Pattiasina; Jems Sopacua (Intelektual Pustaka Media Utama, 2023)
Value clarification technique (VCT) and teaching and contextual learning (CTL) are learning models that are rarely compared in history learning. Hence, the purpose of this study was to find: i) The differences in student learning outcomes using the VCT model and the CTL learning model; ii) Differences in student learning outcomes between the use of the VCT learning model and CTL learning model for students who have high learning motivation; iii) Differences in learning outcomes between the use of VCT and CTL learning models for students who have low learning motivation; and iv) The interaction effect between the use of learning models and students' learning motivation on learning outcomes. This study employed a quasi-experimental quantitative approach with a 2×2 factorial design. The data analysis technique used a two-way analysis of variance at a significance level (α) of 0.05. The population in this study was all students of class X of social science (IPS). The study's research showed that: i) There were significant differences in learning outcomes between students who used the VCT and CTL learning models; ii) There were differences in learning outcomes between the used of the VCT and CTL learning models for students who have high learning motivation; iii) There were differences in learning outcomes between the used of the VCT and CTL learning models for students who have low learning motivation; and iv) The used of the VCT and CTL learning models for students with high learning motivation was associated with better learning outcomes.